The Influence of Power Dynamics on Fostering Religious Tolerance in Early Childhood Education - Ulfah, Fitria (Jurusan Pendidikan Islam Anak Usia Dini, 2024)
This research seeks to dig deeper into the relationships built in the learning process at Darul Hanifah Kindergarten, especially related to religious tolerance because the religions adhered to by students attending Darul Hanifah Kindergarten are heterogeneous (Islam and religious beliefs). This research uses a qualitative case study approach. The case study method was chosen because there were cases of religious diversity/beliefs held by Darul Hanifah Kindergarten students. Observation, interviews, and documentation are data collection techniques. These three techniques were chosen to strengthen the data obtained. Meanwhile, the data analysis technique chosen in this research is data triangulation, so that the validity of the existing data can be recognized. The subjects of this research were the principal, teachers, and students of Darul Hanifah Kindergarten. Religious tolerance between students, teachers, school principals, and parents is well established. Children understand that around them there is diversity in terms of religion but this does not make them different and separate themselves in the learning process. However, it cannot be denied that teachers' involvement in instilling tolerance among children is quite dominant.